Preclinical differential diagnostics of anorexia nervosa and dissociative food refusal: the rating scale - Safonov, D. M.; Gorodokin, A. D. (Journal of Education, Health and Sport, 2019)
In order to develop the rating scale for preclinical differential diagnostics of anorexia nervosa and dissociative food refusal, a retrospective study of two groups of patients with established diagnoses of anorexia nervosa (21 patients) and «mixed (conversion) dissociative disorder» with refusal to eat (23 female patients) were examined. As a result, the express-test for the differential diagnosis of anorexia nervosa and dissociative disorders with the refusal of food was developed, it can be used in the first contact of the patient and the doctor.